Exploring the Impact of Social Support on Tuberculosis Treatment: A Thematic Review - Syamsir, Syamikar Baridwan; Setiawan, Agus; Supriyatno, Heru; Yudanagara, Bani Bacan Hacantya; Natashia, Dhea; Mar'ah, Novya Ashlahatul (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Tuberculosis (TB) remains a critical global health issue, characterized by significant morbidity and mortality rates. Recent research highlights the potential of social support interventions to enhance TB treatment outcomes and improve patient quality of life. This study examines the positive effects of social support interventions on TB patients throughout their treatment process. Method: Utilizing a traditional review approach, this study applies thematic analysis to synthesize findings from the literature. The review encompasses 17 articles selected from reputable databases, including PubMed, Wiley Online Library, ProQuest, and Google Scholar, based on predefined inclusion criteria. These articles underwent quality assessment using the Critical Appraisal Skills Programme (CASP) tool. The PRISMA flowchart provided transparency in the selection process. Results: Key themes identified through the analysis include treatment adherence, psychological well-being, motivation to recover, health-related quality of life, prevention of TB transmission, successful TB treatment, and self-efficacy to recover. Conclusion: The findings suggest that social support interventions can play a crucial role in addressing the persistent challenges of TB management globally.